Natura’s market strategy to enter Czech Republic - Schneeweissová, Adéla (2024)
The global shift towards sustainability in the cosmetic industry, particularly in European markets, presents an opportunity for Natura to expand its market share and establish a strong presence in Europe. This thesis aims to investigate consumer behavior in purchasing and using cosmetic products and propose a marketing strategy for Natura's entry into the Czech market. The thesis is divided into theoretical and practical parts. The theoretical part explores international marketing concepts and global trends within the beauty industry, focusing on the rising importance of natural cosmetics and evolving consumer behaviors. The practical part involves primary research to gain insights into Czech consumers' purchasing habits, values, and attitudes towards cosmetic products and sustainability. These findings serve as the foundation for the marekting strategy proposal.